2022
DOI: 10.1111/psyp.14218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic autonomic nervous system states arise during emotions and manifest in basal physiology

Abstract: The outflow of the autonomic nervous system (ANS) is continuous and dynamic, but its functional organization is not well understood. Whether ANS patterns accompany emotions, or arise in basal physiology, remain unsettled questions in the field. Here, we searched for brief ANS patterns amidst continuous, multichannel physiological recordings in 45 healthy older adults. Participants completed an emotional reactivity task in which they viewed video clips that elicited a target emotion (awe, sadness, amusement, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Furthermore, these findings are consistent with a complementary analysis of continuous self-report data acquired in the framework of this study showing how autonomic system fluctuations are related to acute peak experiences and increases in well-being following DMT administration compared to placebo (Bonnelle et al, 2024). The parasympathetic and sympathetic systems play a crucial role in shaping human emotions (Pasquini et al, 2022) and social behavior (Critchley and Harrison, 2013) through direct and indirect neural pathways underlying interoceptive processes and the homeostatic control of internal bodily states (Critchley and Harrison, 2013; Damasio and Damasio, 2022). We hope that our findings will stimulate future clinical studies elucidating the role of autonomic changes in predicting outcomes following psychedelic therapy (Bonnelle et al, 2024), as well as multimodal neuroscience studies exploring the dynamic integration of bodily signals within specific brain circuits under acute psychedelic administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, these findings are consistent with a complementary analysis of continuous self-report data acquired in the framework of this study showing how autonomic system fluctuations are related to acute peak experiences and increases in well-being following DMT administration compared to placebo (Bonnelle et al, 2024). The parasympathetic and sympathetic systems play a crucial role in shaping human emotions (Pasquini et al, 2022) and social behavior (Critchley and Harrison, 2013) through direct and indirect neural pathways underlying interoceptive processes and the homeostatic control of internal bodily states (Critchley and Harrison, 2013; Damasio and Damasio, 2022). We hope that our findings will stimulate future clinical studies elucidating the role of autonomic changes in predicting outcomes following psychedelic therapy (Bonnelle et al, 2024), as well as multimodal neuroscience studies exploring the dynamic integration of bodily signals within specific brain circuits under acute psychedelic administration.…”
Section: Discussionmentioning
confidence: 99%
“…The positive voltage EKG was then processed via a wavelet transform, and then peaks where detected using the findpeaks function in MATLAB with manually adjusted minimum height (7,500 microvolts) and minimum inter-beat distance (0.45 seconds) (Goldberger et al, 2000; Moody and Mark, 2001; Rosas et al, 2023). Subsequently, continuous heart rate was estimated in beats per minute (bpm) as follows: where HR t is the instantaneous heart rate, 60 reflects the average heart rate in bpm, and RR ij reflects the interval in seconds between subsequent R-peaks i and j (Pasquini et al, 2022). Continuous heart-rate estimates were down-sampled from 250 Hz to 0.5 Hz, the same sampling frequency as fMRI data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, brain and body are undeniably intrinsically and dynamically linked; perceptions, emotions, and cognitions not only influence, but also respond to the state of the body (7), as intuited by William James over a century ago (8) and emphasized by the embodied approach to cognitive neuroscience (9). The importance played by the Autonomic Nervous System (ANS) -particularly at the cardiac level -in emotional experiences and affective states is becoming increasingly recognized (10)(11)(12). Although the centrality and specificity of the autonomic response is still subject to debate, recent work importantly demonstrated that cardiac sympatho-vagal activity may initiate emotional responses preceding neural dynamics (13).…”
Section: Introductionmentioning
confidence: 99%